2020
DOI: 10.3390/polym12010196
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Extender Particle Size on the Glass Transition Temperature of Model Epoxy Coatings

Abstract: Inorganic extenders are important constituents of 2K thermosetting epoxy-amine coatings and their physical properties play an important role in the final properties of the organic coatings. The effects of extender particle size and loading (i.e., the amount of extender in component A or in the total formulation) on the glass transition temperature (Tg) of model epoxy-amine coatings were studied in this work with differential scanning calorimetry (DSC) and dynamic mechanical analysis (DMA). The obtained results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…An experimental investigation of Preghenella et al [59] showed that water absorbed by the neat epoxy can also cause significant T g depression. Moreover, the dependence of T g and peak value of tan δ on the fumed silica content in epoxy composites reported by these authors was similar to that reported by Sun et al [58] and Bashir et al [52]. Dermani et al [60] studied the effect of ionic liquid (IL) modified graphene oxide (GO) addition on the mechanical properties of model epoxy-amine coatings.…”
Section: Investigating Interfacial Interactions In Filled Polymers With Dmasupporting
confidence: 83%
See 2 more Smart Citations
“…An experimental investigation of Preghenella et al [59] showed that water absorbed by the neat epoxy can also cause significant T g depression. Moreover, the dependence of T g and peak value of tan δ on the fumed silica content in epoxy composites reported by these authors was similar to that reported by Sun et al [58] and Bashir et al [52]. Dermani et al [60] studied the effect of ionic liquid (IL) modified graphene oxide (GO) addition on the mechanical properties of model epoxy-amine coatings.…”
Section: Investigating Interfacial Interactions In Filled Polymers With Dmasupporting
confidence: 83%
“…Using model epoxy-amine coatings, Bashir et al [52] analyzed the effect of micrometersized commercial feldspar on the T g of coatings. DSC was mainly used in this study, but DMA also provided important insights into the interfacial interaction of epoxy resin with feldspar.…”
Section: Investigating Interfacial Interactions In Filled Polymers With Dmamentioning
confidence: 99%
See 1 more Smart Citation
“…10 With increasing concentration of micro or nanoparticles in a filled polymer, the value of the peaks, typically, reduces due to increased interfacial interactions. 15,[38][39][40] The peak area and peak width, indicative of overall energy dissipation during the transition, vary across the samples. Notably, sample H3F, which combines both MAPP and GNP with 10% glass fiber, exhibits the highest energy dissipation, as evidenced by its peak area of 51616.5 MPa C. For the samples with the sample H4F, despite having a higher GNP content of 1%, do not show a proportional increase in energy dissipation, suggesting that merely augmenting the GNP content might not linearly enhance this property.…”
Section: Loss Modulusmentioning
confidence: 99%
“…Varying chemical procedures are utilized in combining polymeric matrices with nanoparticles. These procedures include melt and solution intercalation, in situ and emulsion polymerization [36] , [37] , [38] , [39] . Relative to dispersion and distribution of nanoparticles’ in PNCs, both solution intercalation and situ polymerisation are perceived excellent for PNCs fabrication.…”
Section: Pnc Coatings Properties and Classificationmentioning
confidence: 99%